Getting Engaged: “Public” Engagement Practices for Researchers - Kathryn A. Stofer (EDIS)
This 5-page fact sheet is part of the Getting Engaged series that aims to help readers become more comfortable with engaging various stakeholder audiences. It is designed for agriscience, natural resources, or other science and engineering faculty with primarily natural or physical science backgrounds who want to get started in stakeholder engagement. Written by Kathryn A. Stofer and published by the Department of Agricultural Education and Communication, February 2017.